Stabilizability and Disturbance Rejection with State-Derivative Feedback - Moreira, Manoel R. [UNESP]; Mainardi Junior, Edson I. [UNESP]; Esteves, Talita T. [UNESP]; Teixeira, Marcelo C. M. [UNESP]; Cardim, Rodrigo [UNESP]; Assuncao, Edvaldo [UNESP]; Faria, Flavio A. [UNESP] (Hindawi Publishing Corporation, 2010)
In some practical problems, for instance in the control of mechanical systems using accelerometers as sensors, it is easier to obtain the state-derivative signals than the state signals. This paper shows that (i) linear time-invariant plants given by the state-space model matrices {A, B, C, D} with output equal to the state-derivative vector are not observable and can not be stabilizable by using an output feedback if det(Lambda) = 0 and (ii) the rejection of a constant disturbance added to the input of the aforementioned plants, considering det (A) not equal 0, and a static output feedback controller is not possible. The proposed results can be useful in the analysis and design of control systems with state-derivative feedback.